Bartonella endocarditis: a culture-negative endocarditis clinical case report - Cordeiro, Aida (2008)
The diagnosis of infectious endocarditis is based on identification of the causal agent and evidence of valvular alterations seen on cardiac ultrasound. Cases of culture- negative endocarditis are a clinical challenge, because they present frequently with a subacute or chronic evolution and need other techniques for detection of the causative microorganism.Bartonella sp. is an increasingly more frequent cause of culture- negative endocarditis, and the diagnosis is based on an epidemiological history and serological tests. The authors present a case of a woman with a prosthetic valve and several months history of fever and pancytopaenia, with negative cultures and serology positive for Bartonella spp. A revision of the approach for diagnosis of the culturenegative endocarditis, specifically cases due to Bartonella sp., is reported.